2020
DOI: 10.3390/jcm9041240
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on the Effect of Dexamethasone on the Sugammadex Reversal of Rocuronium-Induced Neuromuscular Block

Abstract: Sugammadex reverses the rocuronium-induced neuromuscular block by trapping the cyclopentanoperhydrophenanthrene ring of rocuronium. Dexamethasone shares the same steroidal structure with rocuronium. The purpose of this study was to evaluate the influence of dexamethasone on neuromuscular reversal of sugammadex after general anesthesia. Electronic databases were searched to identify all trials investigating the effect of dexamethasone on neuromuscular reversal of sugammadex after general anesthesia. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Research into rocuronium mainly focuses on its effects on neuromuscular aspects ( Koo et al, 2020 ; Zhang et al, 2019 ) and rarely on lung cancer cell function. We found that rocuronium inhibited lung tumor cell proliferation at regular and high-dose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Research into rocuronium mainly focuses on its effects on neuromuscular aspects ( Koo et al, 2020 ; Zhang et al, 2019 ) and rarely on lung cancer cell function. We found that rocuronium inhibited lung tumor cell proliferation at regular and high-dose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a metaanalysis on the effect of dexamethasone on the sugammadex reversal of rocuronium-induced neuromuscular block confirms the results discussed above. No effect was observed regarding the time required to extubate patients following general anesthesia or the time required for the neuromuscular reversal of sugammadex [31,32]. If taken 2/3 h before inducing anesthesia, a single dose of dexamethasone 8 mg reduced the rocuronium-induced block by 15-20%.…”
Section: Complementary Drugs To Propofol and Fentanylmentioning
confidence: 95%